2021
DOI: 10.1371/journal.pgen.1009360
|View full text |Cite
|
Sign up to set email alerts
|

CRMP/UNC-33 organizes microtubule bundles for KIF5-mediated mitochondrial distribution to axon

Abstract: Neurons are highly specialized cells with polarized cellular processes and subcellular domains. As vital organelles for neuronal functions, mitochondria are distributed by microtubule-based transport systems. Although the essential components of mitochondrial transport including motors and cargo adaptors are identified, it is less clear how mitochondrial distribution among somato-dendritic and axonal compartment is regulated. Here, we systematically study mitochondrial motors, including four kinesins, KIF5, KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Using our long-term imaging device, we were able to extract the experimental probability distribution for organelle addition along the axon and use the values to predict the location of a new mitochondrion addition between a pair of adjacent preexisting mitochondria in a growing neuron. Multiple factors could determine the addition of new mitochondria such as the ratio of molecular motors ( Sure et al, 2018 ; Chen et al, 2021 ), local cytoskeleton ( Sood et al, 2018 ), local calcium concentration ( Wang and Schwarz, 2009b ), new docking sites ( Cai and Sheng, 2009 ), and/or reactive oxygen species ( Debattisti et al, 2017 ; Liao et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using our long-term imaging device, we were able to extract the experimental probability distribution for organelle addition along the axon and use the values to predict the location of a new mitochondrion addition between a pair of adjacent preexisting mitochondria in a growing neuron. Multiple factors could determine the addition of new mitochondria such as the ratio of molecular motors ( Sure et al, 2018 ; Chen et al, 2021 ), local cytoskeleton ( Sood et al, 2018 ), local calcium concentration ( Wang and Schwarz, 2009b ), new docking sites ( Cai and Sheng, 2009 ), and/or reactive oxygen species ( Debattisti et al, 2017 ; Liao et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal domain of CRMP2 binds to the TPR domains of KLC1 and transports the Sra-1/ WAVE1 complex during axon formation (Kawano et al, 2005). It also regulates the microtubule organization in C. elegans neurons, which is essential for the KIF5/UNC-116 dependent axonal transport of mitochondria (Chen et al, 2021). CRMP2 is phosphorylated by CDK-5, GSK3β and Rho-kinase at multiple residues at the C-terminal domain and dephosphorylated by PP2A (Nakamura F. et al, 2020).…”
Section: Phoshoregulation Through the Adaptors Of Kinesin-1mentioning
confidence: 99%
“…There are five homologous CRMP genes, of which CRMP2 (previously known as CRMP62) shares significant homology with the unc33 gene of C. elegans. CRMP2/Unc-33 helps in Kif5A/Unc-116 mediated transport of mitochondria in C. elegans neurons by organizing stable microtubule bundles around the cell body and along the axons (Chen et al, 2021). CRMP2 also aids in the polarized sorting of proteins in the neurons by regulating Kif1A (Maniar et al, 2012).…”
Section: Phosphoregulation Of Kinesin-3mentioning
confidence: 99%
“…UNC-119 is a highly conserved protein that acts as a cytoskeleton organizer in neurons (Maduro et al, 2000; Knobel et al, 2001; Manning et al, 2004; Materi and Pilgrim, 2005; He et al, 2020). A recent study reported that unc-119 functions together with unc-44/Ankyrin and unc-33/Crmp to regulate dendrite polarization, likely through control of actin and microtubule organization, respectively (Hedgecock et al, 1985; Otsuka et al, 1995; Otsuka et al, 2002; Boontrakulpoontawee and Otsuka, 2002; Tsuboi et al, 2005; Zhou et al, 2008; Maniar et al, 2011; Norris et al, 2014; He et al, 2020; LaBella et al, 2020; Chen et al, 2021). Consistent with this, we found that animals carrying mutations in either unc-44/Ank or unc-33/Crmp exhibit PDA differentiation defects similar to those seen in unc-119 mutants (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%